Relationship Between Smartphone Addiction and Emotional Dysregulation on Early Childhood - Jhoni Warmansyah; Setri Monalisa; Khairunnisa Khairunnisa; Lailatul Fadillah; Afriyane Ismandela; Dinda Fatma, Nabila; Widya Putri, Pratiwi (Annual Conference on Islamic Early Childhood Education (ACIECE), 2022)
One aspect that can affect emotion dysregulation is the smartphone addiction. This study aims todetermine the relationship between smartphone addiction with emotion dysregulation early childhood.This type of research uses a quantitative approach with correlational methods. The sampling techniqueused total sampling with 40 children. Data collection techniques using a questionnaire. The data analysistechnique uses the product-moment correlation test. Findings of this study show that there is arelationship between smartphone addiction with emotion dysregulation early childhood. Smartphoneaddiction has a positive relationship with emotional dysregulation in early childhood. Its mean, thehigher the smartphone addiction level in children, the higher the emotional dysregulation in earlychildhood.